Tenets of protection from progression to AIDS: lessons from the immune responses to HIV-2 infection. - Leligdowicz, A; Rowland-Jones, S (2008)
In the past 25 years, life survival curves of many countries have been remodeled owing to HIV infection. Both HIV-1 and HIV-2 can cause AIDS, yet patients infected with HIV-2 fare much better clinically and most will never experience detrimental effects of the infection. Despite over two decades of comprehensive research into vaccine development, a prophylactic vaccine is not yet realized. An essential missing link in the innovation of a successful vaccine strategy is the description of a favorable immune response that abolishes virus replication. Lessons learned from studying the role of the immune system in the long-term nonprogression characteristic of HIV-2 infection will offer insight into how a balanced immune response can protect from the destruction of the immune system associated with chronic HIV-1 infection.